2020
DOI: 10.1080/16549716.2019.1704540
|View full text |Cite
|
Sign up to set email alerts
|

To start or to complete? – Challenges in implementing tuberculosis preventive therapy among people living with HIV: a mixed-methods study from Karnataka, India

Abstract: Background: Isoniazid preventive therapy (IPT) has been shown to reduce the risk of tuberculosis (TB) among people living with HIV (PLHIV). In 2017, India began a nationwide roll-out of IPT, but there is a lack of evidence on the implementation and the challenges. Objectives: Among PLHIV newly initiated on antiretroviral therapy (ART) from January 2017 to June 2018, to: (i) assess the proportion who started and completed IPT and (ii) explore reasons for non-initiation and non-completion from health-care provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
106
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(112 citation statements)
references
References 30 publications
5
106
1
Order By: Relevance
“…The most serious, very rarely reported adverse reactions to INH were seizures, psychiatric symptoms [48,64], (peripheral) neuropathy [60,62] and mild to moderate hepatoxicity [46,60]. Very few patients experienced adverse reactions that required therapy interruption [48,60,63].…”
Section: Patient and Community Related Barriersmentioning
confidence: 99%
See 4 more Smart Citations
“…The most serious, very rarely reported adverse reactions to INH were seizures, psychiatric symptoms [48,64], (peripheral) neuropathy [60,62] and mild to moderate hepatoxicity [46,60]. Very few patients experienced adverse reactions that required therapy interruption [48,60,63].…”
Section: Patient and Community Related Barriersmentioning
confidence: 99%
“…Lacking financial and organisational feasibility frequently emerged as barrier theme [15,34,38,44,46,48,50,54,58,[60][61][62][63]65]. Evidence synthesis revealed that long distance to the clinic [44,60], lacking transport [15,44], and the with transportation associated costs [44,46,48,50,54,63] routinely comprised an obstacle for patients to access therapy and care.…”
Section: Patient and Community Related Barriersmentioning
confidence: 99%
See 3 more Smart Citations